Millets on the Global Stage: Exploring Export Opportunities for Asia - Harsh Saharan; Aditi Mathur; Anubhav Beniwal; I. P. Singh; Yashwant Singh Rathore (International Journal of Economic Plants)
The experiment was conducted during June, 2024 at the Department of Agri-Business Management SKRAU, Bikaner, Rajasthan, India to study the export opportunities of millets for Asia. Millets are nutrient-rich, climate-resilient grains with increasing global demand. However, their domestic consumption in India has declined due to government policies favouring other cereals. This study examines India’s millet export potential using the ARIMA model for forecasting and the Export Potential Indicator (EPI) for market analysis. Results indicate stable export trends with Mexico emerging as a key market. Challenges include processing inefficiencies and trade barriers. Findings highlight India’s role in boosting global millet trade and offer insights for other Asian countries to capitalize on rising demand. Asian countries may boost exports, comprehend market trends, and promote millets as a worldwide super food by conducting astute study and planning. Promoting millets can enhance food security, sustainability, and economic growth.